Implementantion of Law And Utility In Land Electric Registration In Rogojampi Village, Banyuwangi Region - Tamsil; Susilowati, Indri Fogar; Wardhana, Mahendra; Perwitasari, Dita; Astrid Amidiaputri; Author, Ahmad Nailul (Nusantara Journal of Multidisciplinary Science, 2024)
Acceleration of land registration is accommodated through Law No. 11 of 2020 concerning Job Creation, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency issued derivative regulations, namely the Regulation of the Minister of ATR/Head of BPN No. 1 of 2021 concerning Electronic Certificates. The problem of land registration in Banyuwangi is that there are 93,599 unregistered land plots, visiting Rogojampi Village, Rogojampi District, Banyuwangi Regency, the local community said that land registration was said to be too difficult and electronic registration did not provide a sense of security or certainty for the community. So in this case the author will discuss the Implementation of law and the benefits of electronic land registration for the first time faced by the Rogojampi village community. The study chose to resolve the legal issues in this paper using a normative research method, carried out through a legislative approach and a conceptual approach. Certificates as proof of ownership of land rights electronically through 2 authentication factors and encryption methods, a collection of certificates are stored in the database as a history to ensure that what was issued is correct.